Analisis Perbedaan Implementasi Kebijakan Tunjangan Kinerja dengan Kebijakan Remunerasi (Studi Kasus di Politeknik Negeri) - Kusindianing Wijarti; Dyah Sawitri; Jose Rizal Joesoef (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2026)
ABC Polytechnic is one of the public politechnic that implements the Public Service Agency Financial Management Pattern (PK-BLU), which provides flexibility in the management of Non-Tax State Revenue (PNBP). The consequence of the implementation of PK-BLU is a change in the employee compensation system from performance allowances to remuneration. This study aims to analyze the differences in the implementation of performance allowance and remuneration policies and their relationship to the performance of Civil Servants (PNS) at ABC Polytechnic. The study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, documentation studies, and literature studies, then analyzed using the Miles and Huberman interactive analysis model. The results show that performance allowances and remuneration have fundamental differences in aspects of legal basis, funding sources, performance assessment mechanisms, and payment systems. Although the implementation of remuneration has been carried out in accordance with the provisions and considering the principles of proportionality, equality, propriety, and BLU operational performance, this policy shift has not resulted in significant changes in improving employee substantive performance. The visible impact is more dominant in the aspects of administrative compliance and discipline, while changes in mindset, work culture, and work behavior as mandated in bureaucratic reform have not been fully achieved. This finding confirms that the effectiveness of remuneration policies is highly dependent on the clarity of the performance appraisal system, the quality of socialization, and the internalization of performance values within the organization.